PENGARUH BUDAYA ORGANISASI DAN KEDISIPLINAN KERJA TERHADAP KINERJA KARYAWAN BAGIAN PENJUALAN PADA PT. ALTRAK 78 CABANG PEKANBARU - Yogi Yogaswara; Susi Hendriani; Liswar Hamid (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aimed to analyze the effect of partial and simultaneous variables of Influence of Organizational Culture and Discipline Work on Employee Performance Parts Sales at PT. Altrak 78 Branch Pekanbaru .In this study consisted of three variables: the one dependent variable and two independent variables. These variables are Employee Performance (Y), Organizational Culture (X1) Discipline Work (X2). Subjects in this study were employees of PT. Altrak 78 Branch Pekanbaru as 75 people. While the sample is taken as many as 43 people were taken randomly. Sampling by using Slovin (Husein Umar, 2004). Analysis of the data used is by using descriptive and quantitative methods. The results showed that the culture of the organization and discipline of working together have a significant and positive effect on employee performance of sales at PT. Altrak 78 Branch Pekanbaru. This study concluded that the better the culture of the organization and discipline of work jointly applied to the sales employee at PT. Altrak 78 Branch Pekanbaru performance will be better (Setiawan and Waridin 2006).Keywords: Organizational Culture, Discipline Work, Employee Performance